LEGAL CONSIDERATION TOWARDS ECO-TERRORISM AS A NEW FORM OF THE ENVIRONMENTAL LAW CRIME AND TORTS - Rahandy Rizki Prananda; Pulung Widhi Hari Hananto; Muhammad Dzaki Ramadhan; Grandson Tamaro Simanjuntak; Haniff Ahamat (Diponegoro Law Review, 2023)
The global climate action movement has gained diverse support, leading to the rise of both activists and extremists. Eco-terrorism has grown significantly and cause property damage and financial losses over two decades ago. This action concern to further environmental protection through destructive actions. However, glorifying any heroic action often leads to unintended consequences, including harm to certain subject’s property right and environmental damage. This study employs qualitative research with comparative approach to investigate the impacts of eco-terrorism and the evolution of laws addressing this issue at both national and international levels. Additionally, this research intent to examine the consequences of eco-terrorism and consider to put it into a novel form of environmental crime and torts. The research found that current international regulations, such as the United Nations World Charter for Nature and the United Nations Convention on the Law of the Sea, which indirectly address eco-terrorism but lack specificity.  several countries use general provision to handle eco-terrorism regarding violation against civil rights. Even though existing rules able to manage some aspect of eco-terrorism, the new form and adaptive law need to be arranged against this issue in future.